Поглощение оксидов азота ТБФ в пленочном аппарате - Печенко, Тамара Ивановна; Литвиненко, Александр Александрович; Тошинский, Владимир Ильич; Букатенко, Алексей Иванович (НТУ "ХПИ", 2006)
Наведені результати експериментальних досліджень процесу абсорбції оксидів азоту трибутил-фосфатом у плівковому абсорбері під тиском при різній зміні фізико-хімічних і гідродинамічних параметрів.

The results of tentative researches of the absorption process the nitrogen oxides by tributyl phosphate in the climbing-film absorber under the pressure with different changes physic-chemistry and hydrodynamics parameters are brought.
Keywords: трибутилфосфат; абсорбция; коэффициент массопередачи; диффузия; пленочный аппарат